Solar Photocatalytic Degradation of Typical Indoor Air Pollutants Using TiO2 Thin Film Codoped with Iron(III) and Nitrogen - Shuaijie Wang; Xingxing Cheng (Journal of Spectroscopy)
A type of iron and nitrogen codoped titania thin film was prepared by sol-gel method to degrade three typical indoor air pollutants: formaldehyde (HCHO), ammonia (NH3), and benzene (C6H6) under solar light. X-ray diffraction (XRD), UV-Vis spectroscopy, and energy dispersive spectra (EDS) were employed to characterize the photocatalysts. The results showed that the Fe/N codoped TiO2 had a stronger absorption in the visible region than pure, Fe-doped, and N-doped TiO2 and exhibited excellent photocatalytic ability for the degradation of indoor HCHO, NH3, and C6H6. When the three pollutants existed in indoor air at the same time, the removal percentages of HCHO, NH3, or C6H6 after 6 h photocatalytic reaction under solar light reached 48.8%, 50.6%, and 32.0%. The degradation reaction of the three pollutants followed the pseudo-first-order kinetics with the reaction rate constants in the order of 0.110 h−1 for ammonia, 0.109 h−1 for formaldehyde, and 0.060 h−1 for benzene. The reaction rate constant decreased with the increase of initial reactant concentration, which reflected that there was oxidation competition between the substrate and its intermediate during the photocatalytic process.